Economic Growth and E-Commerce: Potential for Digitizing MSMEs in East Java - Dian Rizqi Khusnul Khotimah (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2021)
The social and economic impacts caused by Covid-19 pandemic have changed the way people live. The existence of social activities and shopping due to spread of Covid-19, resulted in switching from an offline system to an online system, including in the case that number of e-commerce increased during the pandemic. In 2020 number of e-commerce businesses in East Java Province grew to 90.31 percent from 19.92 percent in 2019. According to Liu (2013), number of e-commerce businesses will affect economic growth. Pattern of relationship between e-commerce and economic growth needs to be known for an appropriate policy so that both can continue to develop. Furthermore, it is necessary to segment and optimize aspects that support the development of e-commerce and the digitization of MSMEs. This study aims to analyze effect of e-commerce businesses on economic growth in Java, segmenting and optimizing aspects that support development of e-commerce in the locus of Java Island, especially East Java Province, and complete it with an analysis of big data on public response to digital economy in times of pandemic. Method used are a combination of 5 techniques at once, namely regression analysis, thematic map visualization, clustering, spatial analysis, and text mining. Results show that e-commerce affects economic growth of provinces in Java. E-commerce businesses need to continue to be optimized by improving the quality of HDI and internet networks, especially in priority areas for the development of East Java Province. Programs related to digital economy need to be encouraged to harmonize changes in social order with the ability of MSMEs to adapt to digitalization era.